Modelling productivity levels in Ireland and Northern Ireland - Adele Bergin; Séamus McGuinness (The Economic and Social Research Institute (ESRI), 2022)
This study examines sectoral productivity differences in Ireland and Northern Ireland and attempts to understand these by identifying the key determinants of productivity in both economies within a causal framework. While some existing studies have compared Northern Ireland's productivity to that of GB regions, we believe that this is the first comprehensive study to compare productivity in Ireland and Northern Ireland.
Keywords: 330; Produktivität; Branche; Vergleich; Nordirland; Irland